2015
DOI: 10.1590/s0102-865020150090000006
|View full text |Cite
|
Sign up to set email alerts
|

Metformin attenuated the inflammation after renal ischemia/reperfusion and suppressed apoptosis of renal tubular epithelial cell in rats

Abstract: PURPOSE:To investigate the effect of metformin on renal tubular epithelial cell apoptosis and inflammation after kidney ischemia/ reperfusion in rats. METHODS:Eighteen SD rats were randomly divided into three groups: Sham (S), Ischemia/reperfusion (I/R), and Metformin (E).Before establishing the I/R model, group E was administered metformin for three days, while groups S and I/R were administered equal volumes of saline. After three days, a right nephrectomy was performed on all groups, after which the left ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 27 publications
(23 reference statements)
1
21
0
Order By: Relevance
“…It has been confirmed that metformin relieves inflammatory responses following cardiac ischemia and protects cardiac function 11 . Wang et al 12 found that low doses of metformin may attenuate renal I/R injury by increasing the energy supply to the ischemic tissue and reducing the expression of inflammatory cytokines. To our knowledge, no study has investigated the role of metformin in testicular I/R injury.…”
Section: Introductionmentioning
confidence: 99%
“…It has been confirmed that metformin relieves inflammatory responses following cardiac ischemia and protects cardiac function 11 . Wang et al 12 found that low doses of metformin may attenuate renal I/R injury by increasing the energy supply to the ischemic tissue and reducing the expression of inflammatory cytokines. To our knowledge, no study has investigated the role of metformin in testicular I/R injury.…”
Section: Introductionmentioning
confidence: 99%
“…Asghari et al showed that metformin had protective effects on testicular IRI in rats . Moreover, in a renal IRI rat model study, Wang et al reported that metformin reduced inflammation via the increased expressions of interleukin‐6, tumor necrosis factor‐α, transforming growth factor‐β1, and vimentin and loss of E‐cadherin, while it blocked the apoptosis of renal tubular epithelial cells . Using a comparable method to these IRI rat models, we investigated the protective effects of metformin on the ovarian tissue of rats.…”
Section: Discussionmentioning
confidence: 99%
“…In their animal study, Dai et al observed the effective reduction of oxidative liver damage with metformin . Metformin has also been investigated for its antioxidant and anti‐inflammatory properties in certain IRI . Asghari et al showed that metformin had protective effects on testicular IRI in rats .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations